PENGARUH KONTRIBUSI NETO DAN HASIL INVESTASI TERHADAP SURPLUS UNDERWRITING DANA TABARRU’: THE EFFECT OF NET CONTRIBUTION AND INVESTMENT RESULTS ON THE UNDERWRITING SURPLUS OF TABARRU’ FUNDS - Aliefia Azalia; Rizky Maulana; Taufik Hidayat (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study aims to analyze the effect of net contributions and investment returns on the underwriting surplus of tabarru' funds in Islamic life insurance in Indonesia. Islamic insurance, which is based on the principles of mutual protection (takaful) and mutual help (ta'awun), has shown significant growth in recent years, especially amid increasing public awareness of sharia-compliant financial products. This study uses a quantitative approach with multiple linear regression analysis method with OLS (Ordinary Least Square) estimation. The sampling technique used is purposive sampling. The population in this study consisted of 30 sharia life insurance companies registered with the Financial Services Authority (OJK) and the Indonesian Sharia Insurance Association (AASI) during the 2014-2023 period, of which 27 companies met the established criteria. The results showed that net contributions and investment returns had a significant effect partially or simultaneously on the underwriting surplus of tabarru' funds.